Optimalisasi Pengawasan Bidang Pertahanan dalam Rangka Mewujudkan Transparansi pada Sistem Pertahanan Negara - Ramadhan Adi Prasetyo (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2024)
This study is motivated by the government's efforts to realize ideal national defense management by means of transparent supervision and control by a relevant government institution. Because, in the government environment, maladministration, and violations of laws and regulations are still found. The purpose of this research is to comprehensively understand external supervision in the national defense system, the formation of effective supervisory mechanism regulations, internal supervision in the national defense system, and reform of national defense institutions. The research method used is a descriptive analysis approach through literature study. Based on the results of the discussion, it is found that in organizing a good defense system, it is necessary to optimize the control mechanism by conducting effective supervision. This supervision is carried out by government agencies, both the House of Representatives of the Republic of Indonesia, the Inspectorate General within the Ministry of Defense of the Republic of Indonesia and the Indonesian National Army.